Development and control of a unicycle robot with double flywheels. (December 2016) - Chantarachit, Surachat; Parnichkun, Manukid
Abstract: Balancing the unicycle robot is a challenging topic for control and mechanical design. The robot has to robustly balance itself in both longitudinal and lateral directions under uncertain disturbances and inherent non-linear effects. This paper presents the development and control of a unicycle robot which utilizes double-flywheel technique for roll (lateral) control and the inverted-pendulum technique for pitch (longitudinal) control. The non-linear dynamic model is derived by Lagrangian approach. The linearized model is approximated around upright position and identified. The unicycle robot prototype is designed and controlled. Linear quadratic regulator with integral action (LQR + I) is proposed to balance the robot in both directions and compared with the conventional LQR. Simulation and experimental results of balancing control and robot position control are presented. The results significantly show superior performance of LQR + I over LQR.